A Brief Journey into the History of the Arterial Pulse - Nima Ghasemzadeh; A. Maziar Zafari (Cardiology Research and Practice)
Objective. This paper illustrates the evolution of our knowledge of the arterial pulse from ancient times to the present. Several techniques for arterial pulse evaluation throughout history are discussed. Methods. Using databases including Worldcat, Pubmed, and Emory University Libraries' Catalogue, the significance of the arterial pulse is discussed in three historical eras of medicine: ancient, medieval, and modern. Summary. Techniques used over time to analyze arterial pulse and its characteristics have advanced from simple evaluation by touch to complex methodologies such as ultrasonography and plethysmography. Today's understanding of the various characteristics of the arterial pulse relies on our ancestors' observations and experiments. The pursuit of science continues to lead to major advancements in our knowledge of the arterial pulse and its application in diagnosis of atherosclerotic disease.